Comparing well-being and health among rural and urban Indonesian older people: analysis of the related factors - The Maria Meiwati Widagdo; Maria Fransiska Pudjohartono; Meilina Meilina; Angela Rosalia Mete; Adhiyasa Primagupita; Kadek Dewi Armitha Putri Sudarsana (International Journal of Public Health Science (IJPHS), 2022)
Indonesia has the fourth highest population of older people in the world, with Yogyakarta Province having the highest percentage of older people in Indonesia. There is a need to ensure the well-being of older people. This study aimed to compare the well-being and health of older people living in urban and rural areas in Yogyakarta Province, Indonesia, as well as analyze the predictors of well-being. A total of 142 (80 rural and 62 urban) older people aged 60-75 years participated in this study. Well-being was assessed using the WHO-5 Well-Being Index. The factors measured included sociodemographic data (age, sex, educational level, living arrangements, and current employment status), physical function (mobility and balance), cognitive function, depression, independence, and attitude towards aging. Data of the two groups were compared using t-tests and chi-square analysis. Correlations with well-being were analyzed using univariate correlation and multivariate hierarchical regression. The urban group had slightly older age, higher education, lower mobility and balance, higher attitude scores, and higher well-being. Depression was a significant variable in well-being for both communities. Physical capacity was an important factor in urban populations, while well-being in rural areas was better predicted by independence and cognitive function.Keywords: aging, elderly, Indonesia, mental health, older people, physical health, quality of life, rural, urban, well-being